(New page: == Part A == Yes the system is time invariant. <math>x[n] \to (system) \to y[n] = (k+1)^2 x[n] \to (time shift) \to z[n] = y[n-(k+1)] = (k+1)^2 x[n-(k+1)]</math> and then switch the syst...)
 
 
Line 1: Line 1:
 
== Part A ==
 
== Part A ==
 
Yes the system is time invariant.
 
Yes the system is time invariant.
 +
  
 
<math>x[n] \to (system) \to y[n] = (k+1)^2 x[n] \to (time shift) \to z[n] = y[n-(k+1)] = (k+1)^2 x[n-(k+1)]</math>
 
<math>x[n] \to (system) \to y[n] = (k+1)^2 x[n] \to (time shift) \to z[n] = y[n-(k+1)] = (k+1)^2 x[n-(k+1)]</math>
  
and then switch the system and time shift and compare to see if they are equal
+
 
 +
Then switch the system and time shift and compare to see if they are equal
 +
 
  
 
<math>x[n] \to (time shift) \to y[n] = x[n-(k+1)] \to (system) \to w[n] = (k+1)^2 y[n] = (k+1)^2 x[n-(k+1)]</math>
 
<math>x[n] \to (time shift) \to y[n] = x[n-(k+1)] \to (system) \to w[n] = (k+1)^2 y[n] = (k+1)^2 x[n-(k+1)]</math>
Line 12: Line 15:
  
 
== Part B ==
 
== Part B ==
 +
 +
To get the output of Y[n]=u[n-1] from and input of X[n], X[n] = u[n].

Latest revision as of 07:42, 12 September 2008

Part A

Yes the system is time invariant.


$ x[n] \to (system) \to y[n] = (k+1)^2 x[n] \to (time shift) \to z[n] = y[n-(k+1)] = (k+1)^2 x[n-(k+1)] $


Then switch the system and time shift and compare to see if they are equal


$ x[n] \to (time shift) \to y[n] = x[n-(k+1)] \to (system) \to w[n] = (k+1)^2 y[n] = (k+1)^2 x[n-(k+1)] $


Since z[n] = w[n] the signal is time invariant.

Part B

To get the output of Y[n]=u[n-1] from and input of X[n], X[n] = u[n].

Alumni Liaison

Abstract algebra continues the conceptual developments of linear algebra, on an even grander scale.

Dr. Paul Garrett